Unpacking Creativity for Language Teaching - Tin, Tan Bee (Routledge, 2022)
Before unlocking creativity, we must first unpack what it means. In this book, creativity is unravelled from various perspectives and the relevance for language teaching and learning is explored. Tin offers a coherent discussion of creativity, adopting an inclusive and integrated but, at the same time, focused approach to creativity. Divided into 12 chapters, the book covers: • A critical review of the way the term ‘creativity’ is used, defined and written about in various disciplines • Various models and theories of creativity, the product- and process-oriented views of creativity and their relevance for language teaching • Three pillars on which creative language pedagogy should be based • Over 60 practical tasks, applying theoretical arguments and principles of creativity to language teaching and learning. Based on the author’s own practice and research on creativity over the last two decades, the book provides exciting new ideas for scholars and practitioners interested in creativity and creative language pedagogy. The book serves as an important contribution for students, teachers and scholars in the field of applied linguistics, language teaching and education.